Poverty Eradication in Nigeria: A Focus on National Poverty Eradication Programme in Abia State, 2001- 2013 - Eleagu, Greene Ifeanyi (European Scientific Journal, ESJ, 2018)
Poverty has been a huge challenge to Nigeria for a long time as majority of Nigerians live below poverty line. Successive civilian and military governments in Nigeria agreed on the need to eradicate or alleviate this ugly situation. In an attempt to ameliorate the situation, they introduced a number of schemes and programmes. The apparent failure of the various schemes and programmes and the resultant citizen discontent led to the creation of the National Poverty Eradication Programme, NAPEP, in all the states of the federation and the Federal Capital Territory. The broad objective of the study was to empirically evaluate the impact of NAPEP towards poverty eradication in Abia state, through the provision of youth employment. The structuralfunctionalist theory was adopted with an interrogation of relevant documents on financial flows, projects and programmes. The findings suggest that youth unemployment was pervasive. Again, the poverty reduction or alleviation efforts were fraught with corruption. To correct these, the work recommended disbursing monies to beneficiaries through banks. It also suggested, among others, that future efforts should be rural-centred, instead of urban-centred.